Endobronchial tuberculosis mimicking malignancy - Patel, Shahid M (Lung India, 2015)
Endobronchial tuberculosis has a very varied presentation. Diagnosis is often very challenging as typical radiological features are absent and sputum smear for acid-fast bacilli is often negative. However, detection is essential as it may lead to long-term sequelae such as bronchial stenosis. Bronchoscopy is a very useful investigation in such cases. Our case is a rare manifestation of endobronchial tuberculosis as it mimicked malignancy.